Numerical Study of Furnace Processes during Combustion of Off-Design Coals in a 220 t/h Boiler; Thermal Engineering; Vol. 69, iss. 12 - Maltsev K. I. Kirill Ivanovich; Gil A. V. Andrey Vladimirovich; Zavorin A. S. Aleksandr Sergeevich; Lebed D. V. (2022, 2022)
Title screen